The Influence of Capital Expenditure, Size and Leverage on the Financial Independence of Regency and City Governments in Java Island for the 2020-2023 period. - Naurah Azzatia Zahirah; Sri Zulaihati; Dwi Kismayanti Respati (RTTM, 2025)
This research examines how capital expenditures, government size, and leverage influence the financial independence of regencies and cities across Java Island from 2020 to 2023. Regional autonomy emphasizes the importance of independent and efficient financial management to support local development.While Java Island is classified as having a moderate to high level of fiscal independence overall, disparities still exist among its regencies and cities regarding their ability to manage and optimize local financial resources. This study uses a quantitative approach with secondary data obtained from the financial statements of 49 city and regency governments on Java Island, yielding 196 observations in total. The sample was selected using purposive sampling criteria, and the analysis was conducted using multiple linear regression with IBM SPSS software. The findings reveal that government size significantly and positively influences fiscal independence, while capital expenditure and leverage do not have significant individual effects. However, when analyzed collectively, all three variables have a statistically significant impact. These results imply that regions with langer economic and financial scales tend to have greater capacity to generate local revenue and achieve higher levels of financial independence.